Moonshot : the flight of Apollo 11 - Floca, Brian (Atheneum Books for Young Readers, 2019)
Here is the story of the Apollo 11 mission to the Moon -- a story of leaving and returning during the summer of 1969, and a story of home, seen whole, from far away by steady astronauts in their great machines.